Poultry technology toolkit catalogue: Clearinghouse technical report series 016 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2022)
This catalogue describes a suite of proven poultry technologies that advance increased productivity of animal enterprise in Africa. It was developed through a collaborative effort between the Technologies for African Agricultural Transformation (TAAT) Program of the African Development Bank and its Small Livestock Compact coordinated by the International Livestock Research Institute (ILRI). The compilation was also supported by the Project Platform for Agricultural Solutions (ProPAS), an information portal where innovations are systematically characterized for open access over the internet. Both activities are addressing the imperative to better connect proven technologies to those who need them, but each undertakes this goal in a very different 2 manner. Small livestock is one of nine commodity compacts with proven technologies that ensure greater self-sufficiency in protein for food and nutrition security in Africa. Poultry is also targeted as an agro-industrial commodity for processing and trading on domestic and regional markets. The Compact supports a wide variety of stakeholders through capacity development and technological outreach, and this catalogue contributes to that mandate. During the first Phase of the TAAT Program (2018-2021), the Compact introduced and reinforced these technologies in several countries including Ethiopia, Kenya, Mali, Nigeria, Tanzania, Uganda, and Zimbabwe, and plans to expand its reach into 2022 and beyond.